RANCANG BANGUN SISTEM INFORMASI PENGELOLAAN DOKUMEN TANGIBLE CULTURAL HERITAGE - Khafiizh Hastuti; Abu Salam; Budi Handoko; Erwin Yudi Hidayat (Semantik, 2014)
ne"> The geographical position of Central Java which is in the middle of the island of Java,making it aâ€œmeltingpotâ€of cultures as well as the cultural center of Java island. Cultural heritage is divided into tangiblecultural heritage and intangible cultural heritage. Tangible cultural heritage is the work ofthe human body thatcan be moved or moving, or that cannot be moved or did not move. Department of Culture and Tourism ofCentral Java has documented manually cultural heritage but very vulnerable to damage. There are also manycultural heritages that have not been recorded. The process ofdata collection and recording are very difficult,since the datasources are scattered and not well organized. Documentation of cultural heritage in Central Javacan be used as a information system database fora wide range ofcultura linterests in Central Java. The aim isto facilitate and ease The Department of Culture and Tourism of Central Java to documents and recordscultural heritage collections for the category of tangible cultural heritage. In the long-term plan, this system canbe used as a reference by another region, thus forming the national cultural heritage documentation system.Kata kunci: database, multimedia, sistem informasi, tangible cultural heritage